Basic Thinning - Singh, Partap (Indian Forester, 1955)
In marking a thinning foresters seldom agree. They rely on instinct or experience, as little more is understood about thinning beyond the fact that it consists in the removal of some of the worst trees in the crop. The theory of dominance of trees and the commoner mode of diagrammatic representation has added confusion to the paucity of knowledge. In this paper, the present position has been examined, the nature 01 thinnings and their regimes, as related to the laws of growth, studied and simplified, relationship between crop dimensions and differentiations stated, the basis of a relevant tree classification evolved, thinning order list revised, and natural grades of thinning enunciated. The basic foundations of all the rational and empirical methods of thinnings have been analysed and correlated and a few other important questions relating to thinnings explained. The genesis of this paper is that thinning is determined by the number of trees left and classification by the freedom of the crown.